Abnormally differentiated CD4+ or CD8+ T cells with phenotypic and genetic features of double negative T cells in human Fas deficiency - Rensing-Ehl, Anne; Voelkl, Simon; Speckmann, Carsten; Lorenz, Myriam Ricarda; Ritter, Julia; Janda, Ales; Abinun, Mario; Pircher, Hanspeter; Bengsch, Bertram; Thimme, Robert; Fuchs, Ilka; Ammann, Sandra; et al. (Blood, 2014)
Accumulation of CD3(+) T-cell receptor (TCR)??(+)CD4(-)CD8(-) double-negative T cells (DNT) is a hallmark of autoimmune lymphoproliferative syndrome (ALPS). DNT origin and differentiation pathways remain controversial. Here we show that human ALPS DNT have features of terminally differentiated effector memory T cells reexpressing CD45RA(+) (TEMRA), but are CD27(+)CD28(+)KLRG1(-) and do not express the transcription factor T-bet. This unique phenotype was also detected among CD4(+) or CD8(+) ALPS TEMRA cells. T-cell receptor ? deep sequencing revealed a significant fraction of shared CDR3 sequences between ALPS DNT and both CD4(+) and CD8(+)TEMRA cells. Moreover, in ALPS patients with a germ line FAS mutation and somatic loss of heterozygosity, in whom biallelic mutant cells can be tracked by absent Fas expression, Fas-negative T cells accumulated not only among DNT, but also among CD4(+) and CD8(+)TEMRA cells. These data indicate that in human Fas deficiency DNT cannot only derive from CD8(+), but also from CD4(+) T cells. Furthermore, defective Fas signaling leads to aberrant transcriptional programs and differentiation of subsets of CD4(+) and CD8(+) T cells. Accumulation of these cells before their double-negative state appears to be an important early event in the pathogenesis of lymphoproliferation in ALPS patients.
EVALuna2:25697